The Influence of Job Satisfaction on Employee Loyalty with Organizational Commitment as Mediation at Pt Pos Indonesia Karawang - Regina Audita Putri,; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
In the business world, job satisfaction and employee loyalty are needed to achieve company goals. Satisfied and loyal employees tend to contribute more to the company's success. Therefore, this research was carried out in order to find out how job satisfaction and organizational commitment influence employee loyalty. This research uses a quantitative descriptive design where a questionnaire is used as the main instrument in data collection. This research took place at PT Pos Indonesia Karawang. The sample method uses nonprobability sampling with the Slovin formula to obtain a sample of 73 people from a population of 75 employees. The structural equation modeling (SEM) analysis technique with the data processing results of the SmartPLS version 3.0 application shows that job satisfaction and organizational commitment influence employee loyalty directly and indirectly through the mediating role of organizational commitment.